The relevance of verbal prefix formationsin daf lessons - Abdreymova, D.A (SCIENCE and SOCIETY, 2023)
The events described in this poem are not only from our past, but from the present, they are presented in an allegorical way. These mythological plots give life and explain to young people the ecological apathy of nature, our consumption of water, and our power. The lesson of protecting nature was given to the cities. Through each line of this project, the spirit of the reconstruction of the present era was found in the poetic language.
Keywords: story; plot; image; idea; content and form